ONG et Autorité Palestinienne : la « bonne gouvernance » dans un contexte de lutte nationale - Caroline Abu-Sada (Revue des Mondes Musulmans et de la Méditerranée)
Palestinian NGO's have been inundated with international assistance beginning with the September 1993 declaration of principle and yet, have managed to benefit from it without passively accepting the ideologies underlying such aid. The Palestinians have understood, integrated and re-used to their advantage the concepts of transparency, responsibility and legitimacy, all qualities which the NGO's rightly or wrongly demand in exchange. As a means of avoiding state interference, some large aid recipients use their international benefactors to relay criticisms of the Palestinian Authority. The financial aid they providentially receive gives them enough status to pretend to a political role. As a result of such strategies, investors are led to re-evaluate their partnerships in the field, depending on whether the accusations are directed against the Palestinian Authority, or the non-profit, associative sector, traditionally associated with the Palestinian leftwing opposition.